WATERSHED DEVELOPMENT PLANNING BY USING GEOGRAPHIC INFORMATION SYSTEM - Biswas, Joydeep (Journal of Soil and Water Conservation, 2022)
The effectiveness of Geographic Information System (GIS) as a tool in conjunction with Remote Sensing for watershed development planning has been reacertained through its application for "Baramasia Watershed" in Giridhi district of Jharkhand (erstwhile Bihar State). It has helped in using many geomorphic and geographic attributes for developing the management plan of the watershed